Covenantal Pluralism in Australia: A Near Miss with the Conditions of Possibility - Barker, Renae (The review of faith & international affairs, 2025)
This article examines the Australian experience through the lens of covenantal pluralism, a framework requiring freedom of religion and belief, cross-cultural religious literacy, and the cultivation of practical virtues of mutual respect. Drawing on historical and contemporary case studies, it argues that while Australia possesses strong foundations—particularly high levels freedom of religion and respect for human rights at a population level—it nevertheless falls short of achieving covenantal pluralism in practice. Persistent Christian privilege, limited religious literacy, and wavering societal respect for minority faiths highlight these gaps. Australia thus represents a near miss: tantalizingly close yet ultimately unable to fulfil the demanding conditions of covenantal pluralism.